THE UTILIZATION TREE SAP OF BIDURI (CALOTROPIS GIGANTEA) AS THE AEDES AEGYPTI LARVACIDES - Mingle A Pistanty; Jena Hayu Widyasti; Nafisatul Laili (Joseph: Journal of Science and Pharmacy, 2021)
Background: For a period of five years, dengue cases in   Grobogan district have always increased every year, especially   during the rainy season. Although the morbidity rate during that   time period increased from 4.67 to 5.47 per 10,000 population,   the mortality rate decreased from 2.60 to 1.55. The chemical control of the Aedes aegypti DHF vector is constrained by limited operational funds. One alternative is to use biological insecticides. One of the most effective botanical insecticides against Aedes aegypti larvae is Calothropis gigantea or commonly called biduri by the Indonesian people. Purpose: This   study was to determine the benefits of biduri plant sap (Colotropis gigantea) as Aedes aegypti larvacide. Method: This research is a real experimental research design (True Experiment) with a posttest design with a control group (“Posttest Only Control Group Design”) with descriptive and analytical analysis. The analysis used was univariate, bivariate analysis using one way ANOVA to see the benefits of Biduri plant sap (Colotropis gigantea) as Aedes aegypti larvicides. Results: The results showed that 100% mortality was achieved at a dose of 66/1000 ml and 68/1000 ml with a solution concentration of 100%, although at a dose of 62/1000 ml with a solution concentration of 0.62% the killing power was 92.5% and at a dose of 64/1000 ml with a solution concentration of 0.64% the killing power reached 98.3%. This follow-up test was carried out to determine the effective dose in killing Aedes aegypti larvae, namely a dose that could kill 100% of the deaths of 20 larvae tested. Conclusion: The solution of biduri sap (Calotropis gigantea) has a larvicidal effect on the larvae of the Aedes aegypti mosquito. in the 100% toxic category with a solution concentration of 0.66 ml.